Human cytomegalovirus-encoded micrornas can be found in saliva samples from renal transplant recipients - Waters, Shelley; Lee, Silvia; Munyard, Kylie; Irish, A.; Price, Patricia; Wang, B.H. (2020)
Human cytomegalovirus (HCMV) infections are common following renal transplantation and may have long-lasting effects. HCMV can be measured directly by viral DNA or indirectly via host immune responses. HCMV-encoded microRNA (miRNA) may alter the pathobiology of HCMV infections and contribute to the progression of HCMV disease. HCMV-encoded miRNAs can be detected in blood but have not been sought in saliva. We investigated saliva samples from 32 renal transplant recipients (RTR) and 12 seropositive healthy controls for whom immunological data was available. Five HCMV-encoded miRNAs (miR-UL112-5p, miR-US5-2-3p, miR-UL36, miR-US25-2-3p and miR-UL22A) were sought using primer probe assays. HCMV miRNA species were detected in saliva from 15 RTR and 3 healthy controls, with miR-US5-2-3p most commonly detected. The presence of HCMV miRNAs associated with increased T-cell responses to HCMV IE-1 in RTR, suggesting a link with frequent reactivations of HCMV.